Oxidation of Hydrogenated Si(111) by a Radical Propagation Mechanism - Soria, Federico Ariel (2012)
The reactivity of the hydrogenated Si(111) surface toward H2O and O2 was investigated in order to elucidate the mechanism of oxidation of the first silicon bilayer in air. Density functional theory calculations were performed to identify elementary reaction steps and their corresponding activation energy barriers. The perfect surface is unreactive toward H2O and O2 at room temperature as deduced from the high energy barriers found. However, isolated Si dangling bonds, (Si3)Si·, surrounded by SiH groups, readily react with O2 (but not with H2O), producing a silanone intermediate of the form (Si2O)SiO· where one of the silicon back bonds is oxidized. This intermediate is reached after a series of elementary steps with very small activation energy barriers. In the next step, the oxygen atom of the silanone group inserts into a Si–Si back bond, and the surface silicon dangling bond is regenerated as a (SiO2)Si· moiety in which the silyl group has two oxidized back bonds. This initiates a surface chain reaction in which the oxidized silyl group abstracts a hydrogen atom from a neighboring SiH thus producing a new Si dangling bond that is oxidized by O2 in the next step of the chain reaction. This radical propagation mechanism explains the two-dimensional oxide growth in air and the lack of surface SiOH groups. Therefore, the oxidation of the H–Si(111) surface requires the presence of radicals in air that, upon reaction with the hydrogenated surface, produce silicon dangling bonds where the oxidation begins and propagates by hydrogen abstraction from nonoxidized neighboring SiH groups.